The bimodal jitter: a single fibre electromyographic finding - Thiele, Barbara (1974)
The jitter, obtained by SFEMG recordings, mainly reflects the neuromuscular transmission time variability and is usually Gaussian distributed. Here is reported the bimodal distribution of the interpotential intervals, the flip-flop phenomenon. Long flip-flop in cases of reinnervation may indicate alternatively continuous and saltatory nerve conduction. Short flip-flop in normal subjects may be due to muscle fibre interaction or nerve conduction irregularities.